Antifungal activity of selected bioactive compounds against yeast-hyphal transition of oral associated candida species / Mohd Hafiz Mail - Mohd Hafiz, Mail (2017)
Most of fungal infections in oral cavity are caused by Candida spp. Ability to alternate between yeast and hyphae helps dimorphic Candida adhere to epithelial cells and support the biofilm formation and causes oral candidiasis. Oral rinse is used to control the growth of microorganism in the oral cavity. However, most oral rinse contains active ingredients with limited antifungal activity, particularly against hyphae development. Thus, this has encouraged us to search for bioactive compounds from natural sources that are effective against preventing the morphology transition of the dimorphic Candida. Antifungal activity of selected bioactive compounds of bakuchiol, hydroxychavicol, pseudolaric acid B, luteolin and sakuranetin against several species of oral associated Candida were screened before the evaluation on their potency in inhibition of hyphal formation. Identified potent inhibitor was then further investigated on its effectiveness through a brief treatment test on germination, adhesion, cellular morphology and gene expression. Bakuchiol, hydroxychavciol and pseudolaric acid B showed antifungal activity while luteolin and sakuranetin were determined to be inactive against the Candida at concentration below than 1 mg/ml. Hydroxychavicol was determined as a potent inhibitor against hyphal growth of the identified dimorphic Candida species namely, C. albicans. Hydroxychavicol delayed germination process of C. albicans by affecting on the expression of RAS1, NRG1 and HWP1 genes up to 1 hour after the treatment. In addition, the treatment caused slight changes to the cellular morphological structure. However, hydroxychavicol showed poor anti-adherence activity against germinated cells. In summary, hydroxychavicol possessed antifungal activity and was able to prevent the hyphal formation in C. albicans.